INDEX AND STATUS OF SUSTAINABLE FOREST MANAGEMENT IN SOCIAL AND ECONOMIC DIMENCIONS BY SUMBER SARI FOREST FARMER GROUP IN WAN ABDUL RACHMAN GRAND FOREST PARK, LAMPUNG PROVINCE - Amal, Muhammad Ikhlasul; Kaskoyo, Hari; Nurindarwati, Rini; Safe'i, Rahmat (Forestry Study Program University Of Mataram, 2025)
The Index and Sustainability Status play an important role in ensuring the sustainable management of Forest Resources. The objective of this study is to analyze the index value and sustainability status of the management of Wan Abdur Rachman Grand Forest Park in the Sumber Sari Forest Farmers Group in social and economic dimensions. This research employs qualitative and quantitative approaches through observations and interviews. The community sample was obtained using a census method. The data collected were analyzed using multidimensional scaling with the Rapid Fisheries Assessment software. This software is used to assess sustainability status in social and economic aspects of the management. The research results indicate that the forest management in Wan Abdur Rachman Grand Forest Park by Sumber Sari Forest Farmers Group is categorized as quite sustainable. This status is reflected by the high sensitivity values in the community income attribute and accessibility (economic dimension), as well as the community participation attribute in management and the level of education of the community (social dimension). The improvement of road infrastructure, the selection of high-value commodities, training in forest product processing, and the socialization of forest product marketing need to be carried out by the government to achieve a status of very sustainable management.